IMPLEMENTATION OF ERGONOMIC SOLUTIONS FOR CREATING AN INCLUSIVE ENVIRONMENT - Фоменко, О. О. (Art and Design, 2025)
The aim of article is to analyze the implementation of ergonomic solutions for creating inclusive environments. The research methodology is based on the systematization and analysis of existing data, as well as the generalization of the results of previous studies. The conducted analysis allowed for the identification of materials directly related to the research topic. Results. The problem of insufficient research on ergonomic solutions as a means of organizing inclusive environments necessitates detailed studies to understand its specifics. An analysis of the history of inclusive design suggests that the application of ergonomic principles in the process of creating inclusive spaces and products provides not only physical comfort but also psychological safety and forms social integration of the user, corresponding to diverse needs and abilities. The evolution of ergonomics towards inclusive design has formed new paradigms in creating accessible environments. The conducted analysis of the implementation of ergonomic solutions for creating inclusive environments has identified ergonomic solutions that influence the formation of an inclusive environment. The distinctions of using ergonomic solutions as an effective tool for creating inclusive spaces have been clarified and substantiated. Key ways to improve ergonomic solutions to ensure accessibility in the formation of inclusive environments have been revealed. The scientific novelty of the article lies in the definition of ergonomic solutions in the organization of a comfortable and safe inclusive space, which is the main goal of inclusive design in meeting the needs of people with special needs. As a result of the study, a wide range of ergonomic solutions that can be applied to create accessible environments has been identified, and the most promising directions for further research in the field of inclusive design have been established.